Slippery Slopes: Skiing-Related Facial Trauma in Adults. Issue 2 (June 2022) - Galgano, Alissa C.; Cohn, Jason E.; Licata, Jordan J.; Othman, Sammy; Stucker, Fred J.; Bundrick, Paige
Study Design: Retrospective, observational, cross-sectional study. Objective: To determine the incidence of skiing-related facial trauma and to identify their patterns in terms of potential risk factors, mechanism of injury, anatomical location, and degree of severity. Methods: Data was collected using the National Electronic Injury Surveillance System and included snow skiing-related incidents during the years 2009 to 2018. Specifically, injuries limited to the facial region including the head, face, eye(s), mouth, neck or ear(s) were reported. Patients with fractures were further classified by the study variables. Descriptive statistics were used to classify continuous variables while chi-square analysis was used to compare categorical variables. Results: A total of 514 (n = 514) patients met the inclusion criteria within the study period. The majority of injuries were due to concussions (59%), followed by lacerations (18%), fractures (11%), contusions (11%) and dental injuries (1%). Of the fractures seen, the majority were nasal (30%) and cervical spine (30%), followed by midface (27%), mandible (9%) and skull (4%). In our population, head injuries were more common in females (80%) than in males (60%), whereas, mouth injuries were more common in males (8%) than females (1%) [χ 2 = 30.2, p < 0.001]. Conclusions: Skiing-related craniofacial trauma remains a significant mechanism of injury. Our data illustrates a need to correlate these injuries to the use of personal protective equipment. Furthermore, this data calls for the strict implementation of such equipment and the development of safety protocols to further prevent deleterious injury.